The effectiveness of educating mindfulness on anxiety, fear of delivery, pain catastrophizing and selecting caesarian section as the delivery method among nulliparous pregnant women - Lida Ahmadi; Fariborz Bagheri (Tehran University of Medical Sciences, 2017)
Background & Aim: To decrease the rate of caesarean section, complicated intervention for changing behaviors are required. The present study was conducted to evaluate the effectiveness of mindfulness education on anxiety, fear of delivery, pain catastrophizing, and selecting caesarean section as the delivery method among nulliparous pregnant women who referred to Ziaeian Hospital. Methods & Materials: This clinical trial study was conducted on 38 eligible nulliparous pregnant women who referred to the prenatal clinic of Ziaeian Hospital during the time of the study and candidates for caesarean section. Participants were allocated into two groups of 19. The control only participated in childbirth preparation classes, but the intervention group, also participated in 8 mindful childbirth educating sessions based on the educational method of Nancy Bardacke. Data collection tools were Hartman's Childbirth Attitudes Questionnaire, Spielberger's State-Trait Anxiety Inventory and Pain Catastrophizing Scale. Data were analyzed using SPSS software and independent t-test, Chi square test, Fisher's Exact test and covariance analysis. Results: Results of the study showed significant difference between the two studied groups after the intervention regarding their scores of anxiety, fear of delivery, and pain catastrophizing (p < 0.05), that was still statistically significant after adjusting the pre-intervention scores (p < 0.05). Also the number of pregnant women who selecting caesarean section as significantly lower in the intervention group (p < 0.05). In the intervention group, the rate of selecting caesarean section as the method of delivery (p < 0.001), and the scores of anxiety, fear of delivery, and pain catastrophizing (p < 0.05) was significantly reduced after the intervention compared to before the intervention. Conclusion: Considering the primary efficacy of mindfulness education in this study and the mental, biological and social challenges related to pregnancy and delivery and also, relevantly, low attention to the stress preventive programs and cognitive/behavioral issues of pregnancy and its effects on selecting the type of delivery, Health Ministry could use this program as a supplement for delivery preparation classes.